2020
DOI: 10.1126/sciadv.aay2939
|View full text |Cite
|
Sign up to set email alerts
|

Retinoid X receptor alpha is a spatiotemporally predominant therapeutic target for anthracycline-induced cardiotoxicity

Abstract: To uncover the genetic basis of anthracycline-induced cardiotoxicity (AIC), we recently established a genetic suppressor screening strategy in zebrafish. Here, we report the molecular and cellular nature of GBT0419, a salutary modifier mutant that affects retinoid x receptor alpha a (rxraa). We showed that endothelial, but not myocardial or epicardial, RXRA activation confers AIC protection. We then identified isotretinoin and bexarotene, two FDA-approved RXRA agonists, which exert cardioprotective effects. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 46 publications
4
23
0
Order By: Relevance
“…The protective action of bexarotene through LKB1/p70S6K is also conserved in spontaneously hypertensive rats (SHR), where it significantly reduces left ventricular hypertrophy without affecting blood pressure [107]. The cardioprotective action of the rexinoids isotretinoin and bexarotene was highlighted in a recent study showing that activation of endothelial RXRα protects against anthracycline-induced cytotoxicity in zebrafish [108].…”
Section: Retinoid X Receptorsmentioning
confidence: 99%
“…The protective action of bexarotene through LKB1/p70S6K is also conserved in spontaneously hypertensive rats (SHR), where it significantly reduces left ventricular hypertrophy without affecting blood pressure [107]. The cardioprotective action of the rexinoids isotretinoin and bexarotene was highlighted in a recent study showing that activation of endothelial RXRα protects against anthracycline-induced cytotoxicity in zebrafish [108].…”
Section: Retinoid X Receptorsmentioning
confidence: 99%
“…At the end of this pipeline, 204 GBT-candidate lines met the highest stringency of confirmed expression linkage and were classified as ‘GBT-confirmed lines’ ( Figure 2A ). While 57 of these GBT-confirmed lines have been previously published ( Clark et al, 2011a ; Ding et al, 2013 ; Ding et al, 2017 ; El-Rass et al, 2017 ; Ma et al, 2020 ; Westcot et al, 2015 ), 147 of these GBT-confirmed lines are newly characterized in this manuscript and were selected for confirmation based upon their expression pattern and/or homozygous phenotype ( Supplementary file 1 ). A small subset of these GBT-confirmed lines mapped to areas in the genome without annotated transcripts.…”
Section: Resultsmentioning
confidence: 99%
“…Whereas the former type identifies susceptibility genes, the latter type could suggest therapeutic target genes. As shown by studies of GBT419/rxraa, Ma et al (2020) established retinoid X receptor alpha a (rxraa) as a new therapeutic target gene for DIC and reported the underlying mechanism. Through leveraging the integrated loxP sites in the insertional vector, they uncovered a spatiotemporally predominant mechanism of rxraa-based therapy, i.e., that endothelial-specific rxraa activation, but not myocardial-or epicardial-rxraa activation, conferred therapeutic effects on DIC (Ma et al, 2020).…”
Section: Modifier Screening For Isolating Novel Cardiomyopathy Genes mentioning
confidence: 99%
“…As shown by studies of GBT419/rxraa, Ma et al (2020) established retinoid X receptor alpha a (rxraa) as a new therapeutic target gene for DIC and reported the underlying mechanism. Through leveraging the integrated loxP sites in the insertional vector, they uncovered a spatiotemporally predominant mechanism of rxraa-based therapy, i.e., that endothelial-specific rxraa activation, but not myocardial-or epicardial-rxraa activation, conferred therapeutic effects on DIC (Ma et al, 2020). Besides identifying therapeutic target genes via harnessing salutary modifiers, mechanistic studies of deleterious modifiers could also identify a particular way to manipulate the modifier gene to exert therapeutic effects.…”
Section: Modifier Screening For Isolating Novel Cardiomyopathy Genes mentioning
confidence: 99%